Current views on molecularly targeted therapy for lung cancer – a review of literature from the last five years - Rybarczyk-Kasiuchnicz, Agnieszka; Ramlau, Rodryg (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
Lung cancer is the main cause of cancer-related deaths in Poland. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are a new group of agents for non-small-cell lung cancer (NSCLC) patients. Determining the predictive value of activating mutations in the EGFR and ROS-1 genes and ALK rearrangement in non-small-cell lung cancer has enabled the identification of patients likely to achieve true clinical benefits. EGFR-TKIs may produce objective response in more than 60% of patients and prolong progression-free survival to 10 months in mutation-positive patients. No improvement of overall survival was shown in randomized trials. The era of immunotherapy implementing PD-1 and PD-L1 inhibitors has changed the face of lung cancer therapy. We aimed to review the literature on the use of EGFR-TKIs and immunotherapeutic agents for NSCLC patients.